Promuovere le relazioni umane e la giustizia sociale Contributi all'International Conference Social Work Education and Social Development - Campanini, Annamaria; Sanfelici, Mara (Condivisione del sapere nel servizio sociale, 2022)
This volume collects some of the contributions presented at the Italian session of the International Social Work Education and Development Online (ISWED 2021) conference, jointly organised by the International Association of Schools of Social Work (IASSW), and the International Council of Social Welfare (ICSW) and, for the Italian language sessions, by the National Foundation of Social Workers. Its aim is to contribute to the debate that was opened with the creation of the Global Agenda, an initiative taken by the three international organisations in the 2010/2020 decade and renewed for the 2020/2030 decade. In particular, the volume offers reflections on the role of social work in promoting human relations, justice and social solidarity, showing how research, training and professional practice can have an impact in translating the goals guiding the Global Agenda into practice. While the first eight chapters deal specifically with the Italian context and address different themes, such as social work in the face of social emergency, qualitative research as a means of reconstructing social action, perspectives in decision-making processes for the protection of minors, and reciprocity in the exchange between social work and the homeless, the agapic relationship in social work, the production of knowledge in the process of aid, and finally the practices of training in Italian universities, the ninth chapter is dedicated to a historical analysis of social service and training in the State of Espirito Santo in Brazil. Keywords: social work, social justice, social solidarity, human relations, global agenda We believe that this volume can offer an articulate and complex panorama of what is being debated and realised in contemporary social work and can be of interest to all those who, teachers, students, professionals working in the social field.